2010
DOI: 10.1111/j.1463-1318.2010.02357.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum vascular endothelial growth factor A and microsatellite instability in colorectal cancer

Abstract: This study provides some evidence to suggest that patients with an MSI tumour have higher serum VEGF-A levels than patients with an MSS tumour. If further validated, these findings could be of importance when considering the effects of anti-VEGF-A treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…A retrospective analysis by Pogue-Geile et al [ 100 ] revealed that stage II/III dMMR CRC patients significantly derived potential survival benefit from the addition of bevacizumab to standard FOLFOX (HR = 0.52; 95% CI = 0.29–0.94) in contrast to pMMR patients (HR = 1.03; 95% CI = 0.84–1.27). Hansen et al [ 101 ] suggested that CRC patients with dMMR tumors had higher serum VEGF-A levels than those with pMMR tumors. Additionally, adding bevacizumab to adjuvant chemotherapy induced a decrease in Treg percentages but not conventional T cells in the peripheral blood of mCRCs [ 101 ].…”
Section: Predictive Value Of Mmr Status In Crc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis by Pogue-Geile et al [ 100 ] revealed that stage II/III dMMR CRC patients significantly derived potential survival benefit from the addition of bevacizumab to standard FOLFOX (HR = 0.52; 95% CI = 0.29–0.94) in contrast to pMMR patients (HR = 1.03; 95% CI = 0.84–1.27). Hansen et al [ 101 ] suggested that CRC patients with dMMR tumors had higher serum VEGF-A levels than those with pMMR tumors. Additionally, adding bevacizumab to adjuvant chemotherapy induced a decrease in Treg percentages but not conventional T cells in the peripheral blood of mCRCs [ 101 ].…”
Section: Predictive Value Of Mmr Status In Crc Treatmentmentioning
confidence: 99%
“…Hansen et al [ 101 ] suggested that CRC patients with dMMR tumors had higher serum VEGF-A levels than those with pMMR tumors. Additionally, adding bevacizumab to adjuvant chemotherapy induced a decrease in Treg percentages but not conventional T cells in the peripheral blood of mCRCs [ 101 ]. Thus dMMR CRC patients might get significant clinical benefit from bevacizumab owing to their immunosuppressive microenvironment and high serum levels of VEGF-A.…”
Section: Predictive Value Of Mmr Status In Crc Treatmentmentioning
confidence: 99%
“…However, other studies could not validate these findings ( Sinicrope et al , 2011 ). It has been suggested that the effects of anti-VEGF would also vary according to MSI status ( Hansen et al , 2011 ; Kloor et al , 2014 ).…”
mentioning
confidence: 99%
“…There is evidence to suggest that a compensatory mechanism of VEGF-B/VEGFR1 signaling is involved in therapy resistance and anti-VEGF-A treatment [25,26]. It has also been shown that mCRC patients with MSI-H have higher levels of serum VEGF-A [45], that MSI-H tumors have increased angiogenic capacity [46], and that the presence of MSI could influence the effect of anti-VEGF-A therapies [47]. We wanted to investigate whether the clinical effects of the inhibition of VEGF signaling via B could be attributed to the instability of the VEGF-B gene.…”
Section: Discussionmentioning
confidence: 99%